3D in vitro hydrogel models to study the human lung extracellular matrix and fibroblast function - Phogat, Sakshi; Thiam, Fama; Al Yazeedi, Safiya; Abokor, Filsan Ahmed; Osei, Emmanuel Twumasi (Respiratory research, 2023)
The pulmonary extracellular matrix (ECM) is a macromolecular structure that provides mechanical support, stability and elastic recoil for different pulmonary cells including the lung fibroblasts. The ECM plays an important role in lung development, remodeling, repair, and the maintenance of tissue homeostasis. Biomechanical and biochemical signals produced by the ECM regulate the phenotype and function of various cells including fibroblasts in the lungs. Fibroblasts are important lung structural cells responsible for the production and repair of different ECM proteins (e.g., collagen and fibronectin). During lung injury and in chronic lung diseases such as asthma, idiopathic pulmonary fibrosis (IPF) and chronic obstructive pulmonary disease (COPD), an abnormal feedback between fibroblasts and the altered ECM disrupts tissue homeostasis and leads to a vicious cycle of fibrotic changes resulting in tissue remodeling. In line with this, using 3D hydrogel culture models with embedded lung fibroblasts have enabled the assessment of the various mechanisms involved in driving defective (fibrotic) fibroblast function in the lung’s 3D ECM environment. In this review, we provide a summary of various studies that used these 3D hydrogel models to assess the regulation of the ECM on lung fibroblast phenotype and function in altered lung ECM homeostasis in health and in chronic respiratory disease.